2011
DOI: 10.1099/vir.0.034983-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A inhibits the replication of diverse coronaviruses

Abstract: Low micromolar, non-cytotoxic concentrations of cyclosporin A (CsA) strongly affected the replication of severe acute respiratory syndrome coronavirus (SARS-CoV), human coronavirus 229E and mouse hepatitis virus in cell culture, as was evident from the strong inhibition of GFP reporter gene expression and a reduction of up to 4 logs in progeny titres. Upon high-multiplicity infection, CsA treatment rendered SARS-CoV RNA and protein synthesis almost undetectable, suggesting an early block in replication. siRNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
250
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(272 citation statements)
references
References 44 publications
12
250
1
9
Order By: Relevance
“…Cyclosporin A also has activity against coronaviruses. 17 Studies on the mode of action of cyclosporin, and the later developed immunosuppressants from actinomycetes, such as sirolimus (a rapamycin) and FK-506 (tacrolimus), have markedly expanded current knowledge of T-cell activation and proliferation. These agents act by interacting with an intracellular protein (an immunophilin), thus forming a novel complex that selectively disrupts the signal transduction events of lymphocyte activation.…”
Section: Anti-rejection Drugs (Agents That Suppress the Immune System)mentioning
confidence: 99%
“…Cyclosporin A also has activity against coronaviruses. 17 Studies on the mode of action of cyclosporin, and the later developed immunosuppressants from actinomycetes, such as sirolimus (a rapamycin) and FK-506 (tacrolimus), have markedly expanded current knowledge of T-cell activation and proliferation. These agents act by interacting with an intracellular protein (an immunophilin), thus forming a novel complex that selectively disrupts the signal transduction events of lymphocyte activation.…”
Section: Anti-rejection Drugs (Agents That Suppress the Immune System)mentioning
confidence: 99%
“…reported that CsA inhibited the replication of CoVs (SARS–CoV, human 229E CoV, and mouse hepatitis virus (MHV)-A59) using green fluorescence protein (GFP)-expressing recombinant CoVs [25]. Namely, they used Vero-E6 cells and 293/ACE2 cells (these cells stably express the SARS–CoV receptor, ACE2) for infection of SARS–CoV.…”
Section: Csa Inhibits the Replication Of Diverse Covsmentioning
confidence: 99%
“…Therefore, CsA and non-immunosuppressive compounds that bind to Cyps such as NIM811, Debio-025, and SCY-635 inhibit HIV-1 and HCV replication [20,21,22,23,24]. Also, several laboratories have reported that CsA suppresses the replication of various kinds of CoVs [25,26,27]. …”
Section: Introductionmentioning
confidence: 99%
“…CsA reportedly inhibits the replication of various viruses such as human immunodeficiency virus type-1, hepatitis C virus, coronaviruses, vaccinia virus, vesicular stomatitis virus, herpes simplex virus, and BK polyomavirus (9)(10)(11)(12)(13)(14)(21)(22)(23)(24)(25)(26). CsA has antiviral effects on a wide range of viruses; therefore, we hypothesized that CsA would inhibit the multiplication of influenza virus.…”
Section: Discussionmentioning
confidence: 99%